2008
DOI: 10.1121/1.2828205
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and constraints of ambient noise inversion

Abstract: One of the most dominant sources of error in the estimation of sonar performance in shallow water is the geoacoustic description of the sea floor. As reviewed in this paper, various investigators have studied the possible use of ambient noise to infer some key parameters such as the critical angle, geoacoustic properties, or bottom loss. A simple measurement approach to infer the bottom loss from ambient noise measurement on a vertical line array (VLA) is very attractive from environmental and operational pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Regarding volume attenuation, the impact of water absorption at frequencies of 10 kHz has been quantified as a function of array depth. 4 It was observed that for an array below the middle of the water column, the water absorption introduces artifacts in the bottom loss on the order of 1.5 dB at most and typically less than 1 dB. Furthermore, the effect of water absorption is mostly evident at low grazing angles (i.e.…”
Section: Forward Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding volume attenuation, the impact of water absorption at frequencies of 10 kHz has been quantified as a function of array depth. 4 It was observed that for an array below the middle of the water column, the water absorption introduces artifacts in the bottom loss on the order of 1.5 dB at most and typically less than 1 dB. Furthermore, the effect of water absorption is mostly evident at low grazing angles (i.e.…”
Section: Forward Modelmentioning
confidence: 99%
“…2 To the present, inversion of experimental ambient noise data has been approached by heuristic methods 1 (i.e., manual search in the parameter space) and optimization procedures such as genetic algorithms, 3 and studies of sensitivity of the noise field to environmental and array effects are available. 4 Although the Bayesian approach for inversion of ambient noise has been explored in the past with simulated data, 5 the strength of the noise field was not considered in the forward model, and results with experimental data have not yet been published. Two goals are pursued in this paper: First, the Bayesian framework is used to assess the impact of the surface wind speed in the estimation of geoacoustic parameters and their corresponding uncertainties in a study with simulated data.…”
Section: Introductionmentioning
confidence: 99%
“…Marine ambient noise generated at the surface by breaking waves, wind, and rain has received increased interest lately as an acoustic source, allowing the development of passive techniques for surveying the sea bottom, such as Harrison and Simons' technique for bottom-loss estimation [5][6][7][8][9][10] (and its extension to the investigation of bottom layering 11,12 ) and the passive fathometer. [13][14][15][16][17] Harrison and Simons' technique produces an estimate of the bottom loss, as a function of frequency and grazing angle, by beamforming ambient-noise data collected by a vertical line array of hydrophones.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The possibility of dispensing with active sound sources makes the technique particularly attractive, because of the reduced environmental impact, equipment complexity, and power consumption. 10,13 However, the technique can produce inaccurate results in conditions of low wind and/or waves, 14 and whenever the natural-noise field is contaminated by an interferer, such as the engine of a nearby ship. 15 It is shown in this study that ships can actually be used as sources of opportunity, to obtain passive estimates of the bottom reflection loss with Harrison and Simons's technique.…”
Section: Introductionmentioning
confidence: 99%